Forensic Delay Analysis as Evidence of Transaction Costs in Construction Projects. Issue 5 (1st November 2022) - Atanasov, V A; Greenwood, D J; Ross, H; Sanchez, D E
Abstract: Construction projects are characterised by supply chains with multiple contracts and significant transaction costs. An example of these costs is to be found in the management of project delays. The operationalisation and measurement of transaction costs, especially in the construction context, has hitherto proved difficult. The work reported here is concerned with defining and measuring the resources required for the management of contractual disputes relating to project delays. Its main argument is that concepts from transaction cost economics (TCE) theory (bounded rationality, uncertainty, information asymmetry, and opportunistic behaviour) present serious problems for transaction efficiency. This is exemplified in forensic analysis of construction project delays. Data from twelve case studies are analysed, to reveal that up to 90% of time spent on delay analysis was concerned with searching for and validating information which could, ostensibly, be automatically and reliably captured using digital technologies. This research forms part of a wider study that considers the implications of the identified inefficiencies and makes a case for the exploitation of advances in information technology on the more efficient resolution (or even avoidance) of contractual disputes. It concludes that there is a prima facie case for this, and therefore for the reduction in the transaction costs that relate to the management of construction project delays.